Taxonomic signatures of cause-specific mortality risk in human gut microbiome - Salosensaari, Aaro; Laitinen, Ville; Havulinna, Aki S.; Meric, Guillaume; Cheng, Susan; Perola, Markus; Valsta, Liisa; Alfthan, Georg; Inouye, Michael; Watrous, Jeramie D.; Long, Tao; Salido, Rodolfo A.; et al. (Nature communications, 2021)
The collection of fecal material and developments in sequencing technologies have enabled standardised and non-invasive gut microbiome profiling. Microbiome composition from several large cohorts have been cross-sectionally linked to various lifestyle factors and diseases. In spite of these advances, prospective associations between microbiome composition and health have remained uncharacterised due to the lack of sufficiently large and representative population cohorts with comprehensive follow-up data. Here, we analyse the long-term association between gut microbiome variation and mortality in a well-phenotyped and representative population cohort from Finland ( n = 7211). We report robust taxonomic and functional microbiome signatures related to the Enterobacteriaceae family that are associated with mortality risk during a 15-year follow-up. Our results extend previous cross-sectional studies, and help to establish the basis for examining long-term associations between human gut microbiome composition, incident outcomes, and general health status. Gut microbiome composition has a role in health and disease. Here the authors show that microbiome signatures related to the Enterobacteriaceae family are associated with cause-specific mortality risk in a well phenotyped Finish population over a 15-year follow-up.